Phages of non-dairy lactococci: isolation and characterization of ΦL47, a phage infecting the grass isolate Lactococcus lactis ssp. cremoris DPC6860 - Cavanagh, Daniel; Guinane, Caitriona M.; Neve, Horst; Coffey, Aidan; Ross, R. P.; Fitzgerald, Gerald F.; McAuliffe, Olivia (Frontiers in Microbiology, 2014)
Lactococci isolated from non-dairy sources have been found to possess enhanced metabolic activity when compared to dairy strains. These capabilities may be harnessed through the use of these strains as starter or adjunct cultures to produce more diverse flavour profiles in cheese and other dairy products. To understand the interactions between these organisms and the phages that infect them, a number of phages were isolated against lactococcal strains of non-dairy origin. One such phage, ФL47, was isolated from a sewage sample using the grass isolate L. lactis ssp. cremoris DPC6860 as a host. Visualisation of phage virions by transmission electron microscopy established that this phage belongs to the family Siphoviridae and possesses a long tail fiber, previously unseen in dairy lactococcal phages. Determination of the lytic spectrum revealed a broader than expected host range, with ФL47 capable of infecting 4 industrial dairy strains, including ML8, HP and 310, and 3 additional non-dairy isolates. Whole genome sequencing of ФL47 revealed a dsDNA genome of 128, 546 bp, making it the largest sequenced lactococcal phage to date. In total, 190 open reading frames (ORFs) were identified, and comparative analysis revealed that the predicted products of 117 of these ORFs shared greater than 50% amino acid identity with those of L. lactis phage Ф949, a phage isolated from cheese whey. Despite their different ecological niches, the genomic content and organisation of ФL47 and Ф949 are quite similar, with both containing 4 gene clusters oriented in different transcriptional directions. Other features that distinguish ФL47 from Ф949 and other lactococcal phages, in addition to the presence of the tail fiber and the genome length, include a low GC content (32.5%) and a high number of predicted tRNA genes (8). Comparative genome analysis supports the conclusion that ФL47 is a new member of the 949 lactococcal phage group which currently includes the dairy Ф949.